Diagnosis of Public Programs focused on Herbal Medicines in Brazil - Camargo, Ely Eduardo Saranz [UNESP]; Bandeira, Mary Anne Medeiros; Oliveira, Anselmo Gomes de [UNESP] (Natural Products Inc, 2011)
The present study is aimed to diagnose the current public programs focused on herbal medicines in Brazil by means of in loco visits to 10 programs selected by means of questionnaires sent to 124 municipalities that count on herbal medicine services. The main purpose of the implementation of program programs is related to the development of medicinal herbs. 70% of them are intended for the production of herbal medicines and 50% are aimed to ensure the access of the population to medicinal plants and or herbal medicines. The initiative of the implementation of these programs was related to the managers (60%). The difficulties in this implementation were due to the lack of funding (100%) of the programs. In 60% of the programs, the physicians did not adhere to herbal medicine services due to the lack of knowledge of the subject. Training courses were proposed (80%) to increase the adhesion of prescribers to the system. Some municipalities use information obtained from patients to assess the therapeutic efficiency of medicinal plants and herbal medicines. of the programs underway, cultivation of medicinal plants was observed in 90% and 78% of them adopt quality control. In most programs, this control is not performed in accordance with the legal requirements. The programs focused on medicinal plants and herbal medicines implemented in Brazil face sonic chronic problems of infrastructure, management, operational capacity and self-sustainability, which can be directly related to the absence of a national policy on medicinal plants and herbal medicines.
Keywords: Medicinal plants; herbal medicines; public health